1975
DOI: 10.1017/s0022112075000444
|View full text |Cite
|
Sign up to set email alerts
|

The Kelvin-Helmholtz instability of the gas-liquid interface of a sonic gas jet submerged in a liquid

Abstract: It is well known that the small perturbation equation governing steady or mildly unsteady potential flow in a sonic gas jet is nonlinear. However, for a sonic gas jet submerged in a liquid with a disturbance on the gas-liquid interface, it is shown that the transient motion of the gas dominates, and the nonlinear term due to accumulation of disturbances in the basic flow becomes negligible; the condition necessary for the applicability of the linearized governing equation is obtained. It is demonstrated that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…For high-speed gas jets, previous scholars proposed that the K-H instability is the dominant mechanism [21]; however, after the gas is injected into the water, the high speed will rapidly decline after being hindered by the aqueous medium. The dominant mechanism of instability varies with time and space.…”
Section: Analysis Of K-h and R-t Unstable Competition Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…For high-speed gas jets, previous scholars proposed that the K-H instability is the dominant mechanism [21]; however, after the gas is injected into the water, the high speed will rapidly decline after being hindered by the aqueous medium. The dominant mechanism of instability varies with time and space.…”
Section: Analysis Of K-h and R-t Unstable Competition Mechanismmentioning
confidence: 99%
“…Due to the large density gradient and velocity gradient between the gas and the surrounding fluid water, the jets will be governed by Rayleigh-Taylor (R-T) instability and Kelvin-Helmholtz (K-H) instability. Chawla [20,21] studied the K-H instability of the sonic gas jet underwater. He found that pressure disturbance, liquid viscosity, and surface tension affect the stability of the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Chawla 44 investigated the stability of the gas/liquid interface of a sonic gas jet submerged in an infinite mass of liquid under the action of a pressure perturbation, liquid viscosity, and surface tension (see Figure 18). The nonlinear wave equation for the gas jet was subjected to kinematic boundary conditions at the gas/liquid interface.…”
Section: Jet Stability Analysismentioning
confidence: 99%
“…Furthermore, the nonlinear equations were literalized by addition of a perturbation equation and the stability criteria that were applicable for different flows (such as subsonic, sonic and supersonic) were determined. Figure 19 shows the gas jet issuing from a jet orifice of radius r. The flow at the 44 ). orifice was assumed to be uniform, with the gas jet having a constant mean radius equal to the orifice radius.…”
Section: Jet Stability Analysismentioning
confidence: 99%
“…Formation of jet as well as jet length in submerged condition depends on a number of factors such as gas velocity, nozzle geometry, liquid properties, size and depth of the liquid column, etc. 2,3 The theoretical studies dealing with submerged gas jets focused mostly on stability analysis of gas jets in terms of the disturbance generated on the jet surface 4,5 . Koria 6 calculated the non-buoyant jet length of gas jets in a metal bath for both subsonic and supersonic regions.…”
Section: Introductionmentioning
confidence: 99%